Respon Penerima Manfaat Terhadap Komunikasi Pengawasan DPRD: Studi Implementasi Peraturan Walikota Nomor 44 Tahun 2021 Kota Lubuk Linggau - M. Haikal Akbar; Achmad Aminudin; Jatmiko Yogopriyatno (STAI Bumi Silampari, 2025)
This study analyzes the response of beneficiaries to DPRD oversight communication in the implementation of Lubuk Linggau Mayor Regulation Number 44 of 2021 regarding Guidelines for Providing Social Assistance for Condolence and Funeral Money. The research objective is to measure the beneficiaries' perspective on legislative oversight effectiveness using (William N Dunn 2003) five-dimensional framework: effectiveness, efficiency, adequacy, equity, and responsiveness. The research method uses a descriptive quantitative approach with 49 valid respondents from DPRD oversight activities. Instruments include structured questionnaires with 3-point Likert scale, participatory observation, and Focus Group Discussions. Results show overall mean score of 2.255 in